1997
DOI: 10.1093/ps/76.9.1307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental and social factors on incubation behavior, endocrinological parameters, and production traits in turkey hens (Meleagris gallopavo)

Abstract: Hens raised in three different environments were assessed for changes in egg production performance, the rate of incubation behavior expression, and plasma levels of luteinizing hormone (LH) and prolactin for 20 wk following the laying of the first egg. The environments were individual (IFP) or collective floor pens (CFP) and individual battery cages (Cp and Cnp). The hens from three experimental groups (IFP, CFP, and Cp) were transferred from a short (6 h) to a long (14 h) photoperiod, whereas the ones from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, regular egg collection should prevent nest building activity as such, as it is well known that removal of eggs will prevent incubation behaviour expression in birds (Bédécarrats et al., 1997 ; (Guémené et al., 2001 ). On the other hand, commercial initiatives have shown that quail raised in aviaries do, to a certain extent, lay in nesting facilities if appropriate nests are available (Aida Xercavins, IRTA, personal communication, 2023).…”
Section: Assessmentmentioning
confidence: 99%
“…Moreover, regular egg collection should prevent nest building activity as such, as it is well known that removal of eggs will prevent incubation behaviour expression in birds (Bédécarrats et al., 1997 ; (Guémené et al., 2001 ). On the other hand, commercial initiatives have shown that quail raised in aviaries do, to a certain extent, lay in nesting facilities if appropriate nests are available (Aida Xercavins, IRTA, personal communication, 2023).…”
Section: Assessmentmentioning
confidence: 99%
“…Incubation is influenced by a combination of hormonal and other physiological signals, environmental inputs from the eggs or nest (Hall, 1987a;Evans, 1990), and social cues such as presence or absence of a mate Bédécarrats, Guémené, & Richard-Yris, 1997). Previous breeding experience seems to increase an individual's levels of, or responsiveness to, hormonal and environmental signals for incubation and/or chick rearing (Wang & Buntin, 1999;Angelier, Weimerskirch, Dano, & Chastel, 2007;Christensen & Vleck, 2008).…”
Section: Incubationmentioning
confidence: 99%
“…Our observations were in contrast to Robinson et al (1993) where early age at first oviposition was found to impair egg production. It is likely that there is a greater allocation of energy for the ovary at a young age, which may impair ovarian control as observed in broiler breeds (Bedecarrates, et al, 1997). In addition, the limited body reserves would have been depleted by the time of peak egg production (Robinson et al, 1990).…”
Section: Age At First Eggmentioning
confidence: 99%